2021
DOI: 10.1111/jep.13578
|View full text |Cite
|
Sign up to set email alerts
|

Methodological assessment of systematic reviews and meta‐analyses on COVID‐19: A meta‐epidemiological study

Abstract: Rationale, aims, and objectives COVID‐19 has caused an ongoing public health crisis. Many systematic reviews and meta‐analyses have been performed to synthesize evidence for better understanding this new disease. However, some concerns have been raised about rapid COVID‐19 research. This meta‐epidemiological study aims to methodologically assess the current systematic reviews and meta‐analyses on COVID‐19. Methods We searched in various databases for systematic reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Although the median time from search to publication was nine weeks, this ranged from a few days to 39 weeks. Studies have reported substantially shorter acceptance times by journals for COVID-19 publications [ 4 , 68 ], but this has not been sufficient to prevent half the remdesivir reviews being out of date when published. The prominence of preprints during the pandemic has accelerated scientific dissemination [69] , but although most of the reviews published as preprints in our analysis were posted within three weeks of the search date, this was no guarantee of currency, with 45% (4/9) still out of date at time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…Although the median time from search to publication was nine weeks, this ranged from a few days to 39 weeks. Studies have reported substantially shorter acceptance times by journals for COVID-19 publications [ 4 , 68 ], but this has not been sufficient to prevent half the remdesivir reviews being out of date when published. The prominence of preprints during the pandemic has accelerated scientific dissemination [69] , but although most of the reviews published as preprints in our analysis were posted within three weeks of the search date, this was no guarantee of currency, with 45% (4/9) still out of date at time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to apply these metrics to clinical practice for future research. Over the last decade, much effort has been made to promote the reporting of the prediction interval (PI) in a meta-analysis, but only a small proportion of metaanalyses adopt this recommendation in the current literature [9,[59][60][61][62][63]. The PI represents the expected range of the true effects in future studies, making it easier to apply metaanalysis results to clinical practice.…”
Section: Reporting Prediction Intervalsmentioning
confidence: 99%
“…The reliability of the synthesized evidence depends critically on appropriate methods used to perform meta-analyses [3,4]. However, despite the mass production of meta-analyses, it has been found that many meta-analyses need improvements in their methodological quality [5][6][7][8][9][10]. This is a particularly crucial issue in the COVID-19 pandemic because of the concerns about the expedited peer-review process [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are rushing to test pharmacological interventions that may decrease the personal and social burden of the disease as well as producing associated guideline recommendations [ 10 ]. Current literature, however, points to some methodological shortcuts trialist have taken such as low transparency, high heterogeneity, and suboptimal statistical methods [ 11 ]. Trials reportedly have small sample size are single center, and present with redundancy in research questions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%